Complete cleft of the upper limb: A very rare anomaly - C. Bhatt Yogesh; A. O. Harpreet; Bakshi S. Olabanji; A. Vyas Kinnari; S. Ambat Girish; Laad Hitesh; S. Panse Nikhil (Indian Journal of Plastic Surgery)
Background: We describe here a very rare congenital deformity that involves the splitting of the right upper limb with the superior limb articulating with the shoulder joint, and the inferior limb laterally attached to the chest wall. Material and Methods: The child with this rare split limb was treated by transferring the inferior limb on an islanded pedicle to the superior one while creating the hand. Results: A unified limb was reconstructed while creating the hand without any compromise on the existing function and vascularity. The patient is on regular follow-up and further staged procedures have been planned to provide a better functional and aesthetic limb. Conclusion: The congenital deformity described here has not been mentioned in world literature so far and its embryological basis is a matter of discussion. Opinions regarding further management of this anomaly are invited from experts in the field.